2017
DOI: 10.1093/annonc/mdx123
|View full text |Cite
|
Sign up to set email alerts
|

Statistical controversies in clinical research: data access and sharing—can we be more transparent about clinical research? Let’s do what’s right for patients

Abstract: Calls for greater transparency and 'open data access' in clinical research are widespread, from sources including the Executive Office of the President, which in 2013 called for increased access to the results of federally funded research. In 2015, The Institute of Medicine issued a report advocating for a multi-stakeholder effort to foster responsible data sharing, and there are many others. Open science is good for researchers, good for innovation, and good for patients. The question at the center of the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This gap between the intention to share data and the lack of supportive regulatory and policy frameworks can be attributed to the direct or indirect effects connected with data sharing. At a macrolevel, this could be due to issues pertaining to IPR, differences across regulatory guidelines in high-income countries and LMICs, the variations in commercial interests of funding sources, and the potentially high economic benefits from data exclusivity [ 80 - 82 ]. Besides these issues, researchers are concerned about ensuring the privacy and confidentiality of study participants; although the informed consent procedures have provisions to seek participants’ consent for data sharing and secondary use of their data, these are rarely implemented in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap between the intention to share data and the lack of supportive regulatory and policy frameworks can be attributed to the direct or indirect effects connected with data sharing. At a macrolevel, this could be due to issues pertaining to IPR, differences across regulatory guidelines in high-income countries and LMICs, the variations in commercial interests of funding sources, and the potentially high economic benefits from data exclusivity [ 80 - 82 ]. Besides these issues, researchers are concerned about ensuring the privacy and confidentiality of study participants; although the informed consent procedures have provisions to seek participants’ consent for data sharing and secondary use of their data, these are rarely implemented in practice.…”
Section: Discussionmentioning
confidence: 99%
“…These could also hamper the efforts of clinical trial investigators seeking to incorporate specific data-sharing clauses in the informed consent procedures. Moreover, the cost associated with data sharing, potential threats to confidentiality, academic credit, and investigator capacity to standardize data in a shareable manner are some concerns from a researcher’s perspective [ 80 - 82 ]. Our gray literature screening of clinical trial websites showed that not every clinical trial agency is guided by its own data-sharing regulatory document ( Multimedia Appendix 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess willingness to participate in health data networks, we asked whether participants were “comfortable having my electronic health information being a part of a network that includes” six different agencies or data networks: 1) other health care providers involved in my care, 2) all health care providers in my state, 3) social service agencies, 4) mental health services, 5) research networks, and 6) quality improvement networks. Participants rated their responses on a four-point “how true” scale ranging from “Not at all true [1]” to “Very true [4]”. We generated a measure of overall willingness to participate in multi-user data networks by summing the responses to questions about willingness to share data with each of the six potential participants in health data networks.…”
Section: Methodsmentioning
confidence: 99%
“…Networks that support health data and information exchange are at the heart of health IT infrastructure development and are a necessary element of learning health care systems [12], accelerated quality improvement, and more efficient implementation and patient care. The scope of networked data ranges from patient-level clinical trial and research data [34] to genetic data [5678] and electronic health record information [2, 91011]. Network-to-network connectivity and the capacity to exchange health information, including PHI, is maturing.…”
Section: Introductionmentioning
confidence: 99%
“…These have all been reviewed elsewhere. 27,28 The oncology community has also been quite active in the area of data sharing and several platforms have evolved specific to oncology. Oncology-focused data sharing has also been put center stage by former Vice President Joe Biden as part of his Cancer Moonshot program.…”
Section: Current Approaches To Open Data Accessmentioning
confidence: 99%